Computational Structural Modeling of the TTN p.(Arg3936Ter) Variant in a Panamanian Patient with Dilated Cardiomyopathy - Lydier De Gracia; Omar Espinosa; Luis Sotillo; José Cedeño (Gene Clin Genom, 2026)
Background: Truncating variants in TTN are among the most frequent genetic causes of dilated cardiomyopathy. However, TTN encodes multiple tissue-specific isoforms through extensive alternative splicing, and the clinical significance of a given truncating variant can depend critically on which transcript is affected. Objectives: This study pursued three related aims for the TTN NM_133379.5:c.11806C>T; p.(Arg3936Ter) variant, previously identified in a Panamanian patient with dilated cardiomyopathy: (1) to consolidate its clinical interpretation using established genomic evidence and ACMG/AMP criteria; (2) to characterize the domain-level and structural consequence of the predicted truncation, combining protein domain annotation with AlphaFold2-based structural modeling of both the wild-type and truncated protein; and (3) to determine the transcript specificity of this consequence across annotated TTN isoforms and its predicted nonsense-mediated decay (NMD) status. Methods: We integrated variant annotation, population frequency, conservation scores, ACMG/AMP interpretation, InterProScan/Pfam domain annotation, Ensembl VEP consequence annotation across all annotated TTN transcripts, and AlphaFold2/ColabFold structural modeling (with a genuine multiple sequence alignment) of both wild-type and truncated protein fragments (residues 33994100 and 33993935, respectively, of isoform Novex-3, NP_596870.2). Structural similarity between models was assessed by rigid-body superposition (Kabsch algorithm) and independently cross-validated using the RCSB PDB pairwise structure alignment tool (TM-align). Results: The p.Arg3936Ter variant introduces a premature termination codon predicted to generate a truncated titin protein of 3,935 amino acids. Established genetic evidence extreme rarity in population databases and strong evolutionary conservation supported classification as Likely Pathogenic under ACMG/AMP criteria (PVS1, PM2). VEP annotation across 14 curated TTN transcripts showed that this genomic position is intronic in 91% of annotated transcripts and produces a stop-gained consequence exclusively in NM_133379.5 (Novex-3), the transcript used for clinical variant nomenclature. Within this transcript, the variant falls in exon 46 of 46 the final exon and is predicted to escape nonsense-mediated decay. InterProScan identified two immunoglobulin-like (I-set) domains in the encoded fragment; the truncation removes the second domain in its entirety. AlphaFold2 modeling of both the wild-type and truncated fragments (each with a real multiple sequence alignment) showed nearly identical mean confidence (pLDDT 56.5 vs. 55.2) and, on structural superposition, the retained domain aligned with an RMSD of 0.19 Å between wild-type and truncated models, confirming that the shared portion of the protein folds identically and that the only structural difference is the complete absence of the second domain. Conclusion: Established genomic and population-level evidence support a Likely Pathogenic, loss-of-function classification for the TTN p.Arg3936Ter variant. This structural consequence is specific to the Novex-3 isoform (NM_133379.5), escapes nonsense-mediated decay, and is expected to yield a stable truncated protein missing a complete immunoglobulin-like domain a conclusion independently supported by domain annotation, AlphaFold2 modeling of both wild-type and truncated proteins, and quantitative structural alignment.